STUDENT MISCONCEPTION PROFILE IN PROTEIN SYNTHESIS TOPIC USING FOUR-TIER DIAGNOSTIC TEST TECHNIQUE - Ariesta, Shinta Nadya Mega; Susantini, Endang (Berkala Ilmiah Pendidikan Biologi (BioEdu), 2021)
Misconception is students’ misunderstanding in interpreting a concept within scientific theory. Amongst the biological topics that often cause misconceptions is protein synthesis. Protein synthesis is considered as a topic with complex concepts. This research aims to describe the students’ misconceptions profile in protein synthesis topic and describe the causing factors of students’ misconception in protein synthesis topic. This research is descriptive quantitative using four-tier diagnostic test instrument which consisting of 4 tiers, 1st tier is the question with 5 possible answers, 2nd tier is the level of confidence of the answer, 3rd tier is the 5 possible reasons, and 4th tier is the level of confidence of the reason. This research was conducted during the Covid-19 pandemic, which made it impossible to meet directly, so the data was collected online via google form and google meet. The study subjects were 34 students of grade XII MIPA-4 SMA Negeri 1 Gresik. Results showed that 32.37% misconceptions occurred in the protein synthesis topic. The highest misconception was in the concept of RNA characteristics, with the percentage of 65%. Factors that cause misconceptions were the students’ lack of interest in protein synthesis topic, the teacher were too fast in explaining the information, limited selection of learning methods during Covid-19 pandemic, and the information in the textbook was incomplete and difficult to understand. Implementation testing of models, methods, or learning media can be done to reduce students' misconceptions in protein synthesis topic, especially in the concept of RNA characteristic, DNA replication, and translation process.